IMPLEMENTASI NASIHAT RASUL PAULUS TENTANG PERSEMBAHAN YANG BENAR BERDASARKAN ROMA 12:1- 3 BAGI JEMAAT GEREJA ISA ALMASIH SUKOREJO, KENDAL, JAWA TENGAH - Baene, Noferianus; Purwoko, Paulus Sentot; Hendrikus, Hendrikus (Sekolah Tinggi Teologi Kadesi Bogor, 2024)
A true offering is a gift to an honorable person. The word offering can also be interpreted as dedication, surrender, respect, devotion or asking for protection from someone who is considered stronger than oneself. When someone hands over an offering, it contains a confession that the Lord Jesus has looked after us faithfully and perfectly. A true offering should begin with the willingness to offer oneself and one's life completely to God, that is a living and holy offering. Along with this, when Christians attend or attend worship in the midst of church, apart from providing their hearts and minds to commune with God, people must also prepare offerings that will be submitted to God. This is also emphasized in Deuteronomy 16:16-17 where it says